Fe+3-doped TiO2: A combined experimental and computational approach to the evaluation of visible light activity - Yalcin, Yelda; Kilic, Murat; Cinar, Zekiye (ELSEVIER SCIENCE BV, 2010)
The visible light activity of TiO2 particles was improved by Fe3+-doping. In order to characterize and describe the effect of Fe3+-doping on the electronic and structural properties of TiO2, a combination of experimental structural methods and density functional theory (DFT) calculations was used. A series of Fe3+-doped photocatalysts with different Fe3+ contents were prepared by an incipient wet impregnation method, in order to prevent penetration of the dopant cations into the bulk of TiO2. An obvious decrease in the band-gap and a red shift of the absorption threshold were observed by UV-DRS. The Fe3+-doped photocatalysts were characterized by FT-IR, XRD, Raman and XPS. The morphological structure of the photocatalysts was examined by SEM. Energy-dispersive X-ray analysis (EDX) in the SEM was also taken for the chemical analysis of the doped samples. The results indicate substitutional Fe3+-doping of TiO2. In the computational part of the study, a neutral, stoichiometric cluster Ti3O8H4 cut from the anatase bulk structure and three new models for the substitutional Fe3+-doped TiO2 were developed. The DFT calculations were carried out by the hybrid B3LYP functional, by using double-zeta. LanL2DZ basis set. A higher photocatalytic activity for the degradation of 4-nitrophenol was obtained for the Fe3+-doped TiO2 compared to the undoped TiO2. The results of the DFT calculations indicate that the origin of the visible light activity of the Fe3+-doped TiO2 is due to the introduction of additional electronic states within the band-gap. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: TiO2; DFT calculations; Fe3+-doping; 4-Nitrophenol; Heterogeneous photocatalysis; PHOTOCATALYTIC DEGRADATION; DOPED TIO2; RUTILE TIO2; WATER; FE; PERFORMANCE; ADSORPTION; TITANIA; Chemistry; Engineering